Analysis of the Sustainability of Coffee Producing Farms in the Province of Guanentá, Santander - Lemus Riveros, Carlos Felipe; González Santos, Wilson (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The objective of the work was to analyze the sustainability of the coffee producing farms in the province of Guanentá, Santander. The framework methodology was used for the evaluation of the natural resource management system by means of sustainability indicators (MESMIS), and it was evaluated –in addition to the three conventionally accepted elements for sustainability: social, economic, environment– the institutional component, in concordance with new trends in rural development. The results indicate that the dissimilar behavior of sustainability in the six producing farms of the three evaluated municipalities transcends the environment dimension to focus on social, economic and institutional indicators, which with a greater variability given by a higher typical deviation explain the difference among coffee farms.  Based on the results, it is concluded that the farms have a high performance in the environmental dimension related to the coffee culture of special coffees certification as opposed to a high variability in the social indicators. In this regard, the social dimension has the least sustainability and the greatest variability with respect to the other dimensions of sustainability. The multidimensional analysis of sustainability allows us to know the gaps of the coffee producting farms to move towards sustainability and omits the fragmentation contained in the study of a particular dimension.